Effect of storage conditions on fungal community in Crataegi Fructus through DNA metabarcoding - Jingsheng Yu; Yujie Dao; Meihua Yang; Jianping Han; Xiaohui Pang (Medicinal Plant Biology)
Herbs are susceptible to fungal contamination during storage under proper conditions, which affects their quality and safety. Storage time and temperature are two crucial factors that influence the fungal community. In this study, we investigated the impact of both factors on the dynamics of the fungal community in Crataegi Fructus (CF), a medicinal and edible herb in China. The CF materials were stored under two different temperatures (room temperature and 4 °C) and collected at four time points (0, 8, 16, and 24 weeks). DNA metabarcoding was employed to monitor the changes of fungal communities in CF. Results showed that the fungal community in CF samples remarkably changed over the storage period. Significant differences in the relative abundances of dominant genera were observed in CF samples stored at different temperatures. A total of 67 species were identified, including seven potentially toxigenic fungal species, namely Rhizopus microsporus, Penicillium oxalicum, Trichothecium roseum, Candida tropicalis, Penicillium brevicompactum, Beauveria bassiana, and Talaromyces rugulosus. Both storage time and temperature significantly influenced the relative abundances of certain fungi in CF samples, particularly the dominant fungi. This study demonstrates that DNA metabarcoding is an effective method for assessing fungal contamination in CF. It also discusses the effects of storage time and temperature on the fungal community in CF, providing references for the proposal of prevention strategies in practical CF production chains.